Comparison of computed tomography–guided core needle biopsy of pulmonary nodules performed with and without the coaxial technique - Qun-Qun Zhu; Li Zhang; Fengfei Xia; Yi-Bing Shi; Lei Zhu; Xian-Xian Liang (Videosurgery and Other Miniinvasive Techniques)
Introduction: Computed tomography (CT)-guided core needle biopsy (CNB) is a common method for diagnosing pulmonary nodules (PNs). It is often performed using the coaxial technique (CAT) to streamline the process.